2019
DOI: 10.3390/molecules24213987
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Non-Synonymous Single Nucleotide Variations Associated with α-Carbonic Anhydrase II Deficiency

Abstract: Human carbonic anhydrase II (CA-II) is a Zinc (Zn2+) metalloenzyme responsible for maintenance of acid-base balance within the body through the reversible hydration of CO2 to produce protons (H+) and bicarbonate (BCT). Due to its importance, alterations to the amino acid sequence of the protein as a result of single nucleotide variations (nsSNVs) have detrimental effects on homeostasis. Six pathogenic CA-II nsSNVs, K18E, K18Q, H107Y, P236H, P236R and N252D were identified, and variant protein models calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 105 publications
(174 reference statements)
1
27
0
Order By: Relevance
“…This points to distant effects on residue connectivity induced by drug-resistance mutations. Similar long-range effects due to mutations have been reported in previous studies [22].…”
Section: Mutation-induced Changes In Pf Dhfr Intra-protein Communicatsupporting
confidence: 89%
See 3 more Smart Citations
“…This points to distant effects on residue connectivity induced by drug-resistance mutations. Similar long-range effects due to mutations have been reported in previous studies [22].…”
Section: Mutation-induced Changes In Pf Dhfr Intra-protein Communicatsupporting
confidence: 89%
“…Altogether, despite pairwise Pearson's correlation of ∆BC ( Figure S13) failing to group the different mutants based on respective degrees of resistance to pyrimethamine as discussed before [15] (WT: sensitive; SM: low resistant; DM1, DM2: moderately resistant; TM1, TM2: high resistant; and QM: highly resistant), these calculations provided useful clues related to catalytic efficiency. This is expected since DRN analysis highlights differences in intra-protein communication (which relates to protein function) when applied in comparative analysis between WT and mutant [22,37]. These findings further suggest that the pyrimethamine resistance mechanism is based on localized adjustments due to mutations within the Pf DHFR active site and may not correlate to its catalytic activity.…”
Section: Mutation-induced Changes In Pf Dhfr Intra-protein Communicatmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, network analysis is usually performed to determine the pathways that connect the mutation and the active site and aids in the study of allosteric communication [86,94,95]. A recent publication studied six validated non-synonymous single nucleotide variations (nsSNVs) to identify underlying mechanisms responsible for CA-II deficiencies resulting in the phenotype of osteopetrosis with renal tubular acidosis and cerebral calcification [96]. In this study, Sanyanga et al combined MD and DRN [97] analysis and showed that nsSNVs have indirect/allosteric effects, providing greater insights into SNV mechanism of action.…”
Section: Understanding the Allosteric Effects Of Disease And Drug-resmentioning
confidence: 99%